VD_FINDINFO AI 293/10 - 173/2011 vom 7. April 2011 - VD Tribunal cantonal (2011)
AIASSURANCE, RENTE D'INVALIDITÉ, RAPPORT MÉDICAL, NOUVELLE DEMANDE | 28 LAI, 4 LAI, 7 LPGA, 8 LPGA, 87 al. 3 RAI, 87 al. 4 RAI